Brain Lipopolysaccharide Preconditioning-Induced Gene Reprogramming Mediates a Tolerance State in Electroconvulsive Shock Model of Epilepsy - Elham Amini; Mojtaba Golpich; Abdoreza S. Farjam; Behnam Kamalidehghan; Zahurin Mohamed; Norlinah M. Ibrahim; Abolhassan Ahmadiani; Azman A. Raymond (Frontiers Media S.A., 2018)
There is increasing evidence pointing toward the role of inflammatory processes in epileptic seizures, and reciprocally, prolonged seizures induce more inflammation in the brain. In this regard, effective strategies to control epilepsy resulting from neuroinflammation could be targeted. Based on the available data, preconditioning (PC) with low dose lipopolysaccharide (LPS) through the regulation of the TLR4 signaling pathway provides neuroprotection against subsequent challenge with injury in the brain. To test this, we examined the effects of a single and chronic brain LPS PC, which is expected to lead to reduction of inflammation against epileptic seizures induced by electroconvulsive shock (ECS). A total of 60 male Sprague Dawley rats were randomly assigned to five groups: control, vehicle (single and chronic), and LPS PC (single and chronic). We first recorded the data regarding the behavioral and histological changes. We further investigated the alterations of gene and protein expression of important mediators in relation to TLR4 and inflammatory signaling pathways. Interestingly, significant increased presence of NFκB inhibitors [Src homology 2-containing inositol phosphatase-1 (SHIP1) and Toll interacting protein (TOLLIP)] was observed in LPS-preconditioned animals. This result was also associated with over-expression of IRF3 activity and anti-inflammatory markers, along with down-regulation of pro-inflammatory mediators. Summarizing, the analysis revealed that PC with LPS prior to seizure induction may have a neuroprotective effect possibly by reprogramming the signaling response to injury.